The Workers' Health Fund in Eretz Israel Kupat Holim, 1911-1937 - Shvarts, Shifra (Rochester Studies in Medical History, 2002)
The history of Kupat Holim, the health organization of workers in Israel, began at the 2nd Convention of Jewish agricultural workers in Judea in December 1911. Due to the lack of health services within the economic means of the workers, and the refusal of the farmer-employers to extend health services to their employees, the Jewish agricultural workers in Eretz-Israel -- at that time, a distant province of the far-flung Ottoman empire -- decided to establish a workers' health fund (kupat holim in Hebrew). In the years 1912-15, two funds similar to the ones in Judea were also established in the north and center of the country. In the first years, the health funds did not provide workers with medical assistance on their own. Only in 1913, with the outbreak of the First World War, were the health funds transformed from insuring organizations into ones that provided medical assistance services themselves. With the establishment of the General Federation of Labor (1920), the health funds were amalgamated into a single organization -- the Federation's Kupat Holim (1921). The unification of Kupat Holim ultimately determined the organization's future -- transforming it from a small, local, temporary body with a few dozen members into a national entity and a key factor in health services in Israel to this day. This volume seeks to describe the growth of Kupat Holim up to the point where it was transformed into a central health organization in Israel; its relationship with its parent-organization, the General Federation of Labor and its rivalry with its competitor in the health field, Hadassah; its evolution from an organization solely for laborers to one open to all; the efforts on the part of Kupat Holim during the British Mandate (1918-1948) to bring about legislation for a compulsory health insurance law; and the formulation of the basic principle that underlie the work of Kupit Holim to this day -- the principle of national and social responsibility for the provision of equal health services to all. Dr. Shifra Shvarts is the head of the Health Systems Management Department of the Faculty of Health Sciences and School of Management at Ben-Gurion University.